2021
DOI: 10.1111/epi.16892
|View full text |Cite
|
Sign up to set email alerts
|

Early epileptiform EEG activity in infants with tuberous sclerosis complex predicts epilepsy and neurodevelopmental outcomes

Abstract: To study the association between timing and characteristics of the first electroencephalography (EEG) with epileptiform discharges (ED-EEG) and epilepsy and neurodevelopment at 24 months in infants with tuberous sclerosis complex (TSC). Methods: Patients enrolled in the prospective Epileptogenesis in a genetic model of epilepsy -Tuberous sclerosis complex (EPISTOP) trial, had serial EEG monitoring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…If epileptic spasms or focal seizures are suspected but cannot be confirmed clinically or the baseline EEG reveals abnormalities that are nonspecific, the patient should have an eight-to 24-hour video-EEG that includes sleep, which may detect electrographic seizures or interictal epileptiform discharges that have been shown to be strongly predictive of impending epilepsy. 29,30 Early recognition and control of seizures is highly correlated with improved developmental and neurological outcomes, [31][32][33] and pre-emptive treatment with vigabatrin before the onset of clinical seizures may provide additional benefit of preventing or delaying seizure onset in at-risk infants diagnosed with TSC and epileptiform activity on EEG. 34 However, pre-emptive treatment with vigabatrin may not be able to improve developmental and neurological outcomes over that achieved by early recognition and control of clinical seizures alone 34,35 (Category 2A).…”
Section: Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…If epileptic spasms or focal seizures are suspected but cannot be confirmed clinically or the baseline EEG reveals abnormalities that are nonspecific, the patient should have an eight-to 24-hour video-EEG that includes sleep, which may detect electrographic seizures or interictal epileptiform discharges that have been shown to be strongly predictive of impending epilepsy. 29,30 Early recognition and control of seizures is highly correlated with improved developmental and neurological outcomes, [31][32][33] and pre-emptive treatment with vigabatrin before the onset of clinical seizures may provide additional benefit of preventing or delaying seizure onset in at-risk infants diagnosed with TSC and epileptiform activity on EEG. 34 However, pre-emptive treatment with vigabatrin may not be able to improve developmental and neurological outcomes over that achieved by early recognition and control of clinical seizures alone 34,35 (Category 2A).…”
Section: Brainmentioning
confidence: 99%
“…The majority of infants with TSC will experience their first seizure before age one year, 97 and seizure control should be considered a medical emergency in infants with TSC because refractory epilepsy is strongly correlated with poor developmental and cognitive outcomes 31,32,97,98 and earlier recognition and treatment of epilepsy in infancy is associated with better long-term neurological outcomes. 31,33 Routine EEG in asymptomatic infants with TSC should be obtained every six weeks up to age 12 months and every three months up to age 24 months, as abnormal EEG very commonly precedes onset of clinical seizures, 29,30 allowing for the earliest possible intervention (Category 1). It should be noted that the first seizure types to occur in TSC can be infantile spasms, focal seizures, or both, and infantile spasms in TSC are frequently not accompanied by hypsarrhythmia.…”
Section: Epilepsymentioning
confidence: 99%
“…Early appearance of epileptiform discharges was associated with worse developmental outcome. Infants presenting with multifocal interictal epileptic discharges benefited more from preventive VGB treatment in delaying seizure onset than infants with focal EEG findings [16]. Also previously, Gataullina et al [17] has shown that in 3/15 infants diagnosed prenatally with TSC and showing subclinical discharges (sharp waves) before any seizures, VGB prevented the development of seizures until follow-up at 18-36 months.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 74%
“…Ictal abnormalities on EEG recordings predate clinical seizures [8]. Very recently, early epileptiform EEG activity of the patients in EPISTOP were more exactly characterized [16]. Early appearance of epileptiform discharges was associated with worse developmental outcome.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…During full text analysis, additional thirty-one reports were excluded as they either did not meet inclusion or met exclusion criteria ( Figure 1 ). Overall, 19 reports were included in the systematic review [ 2 , 10 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The inclusion and exclusion criteria available for each article are included in Table 1 .…”
Section: Resultsmentioning
confidence: 99%